2017
DOI: 10.1002/jor.23531
|View full text |Cite
|
Sign up to set email alerts
|

Glucose homeostasis influences the risk of incident knee osteoarthritis: Data from the osteoarthritis initiative

Abstract: We aimed to determine if serum measures of impaired glucose homeostasis (glucose concentrations or glycated serum protein, GSP) or systemic inflammation (high-sensitivity C-reactive protein, CRP) are related to incident typical knee osteoarthritis (KOA) or incident accelerated KOA. We conducted a case-control study using the Osteoarthritis Initiative's baseline and first 4 annual visits. All participants had no radiographic KOA at baseline (Kellgren-Lawrence [KL]<2). We classified 3 groups: 1) incident acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…However, the CART analysis enabled us to look at possible interactions that would be infeasible with other statistical analyses because of the limited sample size. For example, we previously found no relationship between glucose concentrations and incident accelerated KOA but the small sample size prevented us from assessing this relationship among older adults, where the CART analysis suggests it may be an important factor . Based on these findings, it may be fruitful to explore the association between fasting glucose levels and incident accelerated KOA among adults over 63.5 years of age.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the CART analysis enabled us to look at possible interactions that would be infeasible with other statistical analyses because of the limited sample size. For example, we previously found no relationship between glucose concentrations and incident accelerated KOA but the small sample size prevented us from assessing this relationship among older adults, where the CART analysis suggests it may be an important factor . Based on these findings, it may be fruitful to explore the association between fasting glucose levels and incident accelerated KOA among adults over 63.5 years of age.…”
Section: Discussionmentioning
confidence: 94%
“…While accelerated KOA represents 22% of incident cases of KOA in the Osteoarthritis Initiative cohort, the small sample size makes it is challenging to study complex interactions among risk factors. Furthermore, the nonlinear association between some risk factors and incident KOA makes this even more challenging with common statistical methods (e.g., multinomial logistic regression). Classification and regression tree (CART) analysis overcomes these issues by using a non‐parametric and nonlinear method to identify the most discriminating risk factor and associated cut point to differentiate two groups (e.g., accelerated KOA or no accelerated KOA) and then continue to find the next best risk factor and cut point .…”
mentioning
confidence: 99%
“…While numerous studies have evaluated AKOA with data from the OAI [1,5,6,3,2,4,10,11] they have all focused on the first four years of the cohort. By studying people with AKOA after the 48-month visit of the OAI, we could explore which modifiable risk factors are consistently present and which risk factors are unique to the timing of incident AKOA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that glucose upregulates aggrecan expression and induces cartilage formation, suggesting that glucose treatment not only restores cartilage function but also stimulates chondrogenesis. Epidemiological evidence indicates that diabetes is an independent risk factor for OA (Courties & Sellam, ; Driban et al, ). Our previous study also showed that high glucose upregulates VEGF‐A expression in human synovial fibroblast cells (Tsai et al, ), a hallmark of angiogenesis that is essential for the development, growth, and progression of OA (Ashraf & Walsh, ).…”
Section: Discussionmentioning
confidence: 99%